Introduction to computing using C++ and object technology - Ford, William H. (Prentice Hall, 1999)
Successful authors William Ford and William Topp have written the first introductory programming book using C++ that concentrates on teaching object design. The authors recognize that program design is one of the most difficult concepts for an introductory programmer. They introduce program design through detailed examples, case studies, and object design methodology and tools such as Unified Modelling Language (UML). The authors carefully walk the reader through the principles of top-down design to produce complete real-world applications.